Highly Angularly Stable Dual-Band Stop FSS for Blocking Satellite Downlink Frequencies - Venkatesh G.; Thottappan M.; Singh S.P. (My University, 2025)
High angular stability dual-band (C- A nd X-band) stop frequency selective surface based spatial filter is proposed in this article for blocking the satellite downlink frequencies. The unit cell of the structure consists of vertical and horizontal dipoles having two folded arms. The transmission coefficient of the filter in the designated satellite frequency bands, i.e., 3.7-4.2 GHz and 7.25-7.75 GHz has been obtained less than-10 dB. The current distribution and the equivalent circuit model of the unit cell have been illustrated to explain the resonance behavior and response of the filter. The proposed structure gives a stable response up to 85° of oblique incidence for both TE and TM polarizations. A prototype of the proposed structure has been fabricated, experimentally tested, and validated with simulation results. © 1964-2012 IEEE.